2021
DOI: 10.5662/wjm.v11.i5.263
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the red reflex: An overview for the pediatrician

Abstract: BACKGROUND Red reflex test (RRT) is a simple, non-invasive method that can be performed easily by pediatricians during the clinical examination in neonatal period, infancy and childhood. Abnormal reflexes can lead to prompt diagnosis of several ocular disorders, with potentially severe consequences on patient’s vision, cognitive function and even life. AIM To underline the contribution of pediatricians to early detection of vision and life threatening diseases by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Red reflex examination of neonates helps in the early detection of severe eye conditions, such as cataracts, retinoblastoma, lens dislocation, strabismus, and glaucoma. 15 Studies have shown that universal newborn screening in the first 6 weeks of life can detect about 50%–75% of congenital cataracts requiring surgery. 16 This enables early surgery before 3 months of age, with improved long-term visual outcomes.…”
Section: Visual Disordersmentioning
confidence: 99%
“…Red reflex examination of neonates helps in the early detection of severe eye conditions, such as cataracts, retinoblastoma, lens dislocation, strabismus, and glaucoma. 15 Studies have shown that universal newborn screening in the first 6 weeks of life can detect about 50%–75% of congenital cataracts requiring surgery. 16 This enables early surgery before 3 months of age, with improved long-term visual outcomes.…”
Section: Visual Disordersmentioning
confidence: 99%
“…The examiner then looks through the ophthalmoscope and focuses on both corneas simultaneously, noting a red reflex in each pupil [18]. A normal test consists of symmetrically bright and round red reflexes in both eyes [19]. Asymmetry of the reflexes may be associated with strabismus, anisometropia, media opacities or cataracts, retinoblastoma, colobomas, and pigment abnormalities of the posterior pole [18,20].…”
Section: Red Reflex Testmentioning
confidence: 99%
“…The test is negative if the appearance is symmetric in both eyes and the reflex is round and bright. Any asymmetry, lack of a red reflex or white or dark defects means positivity of the test, and the infant must be referred to the ophthalmologist for further examination [1,2].…”
Section: Full-term Healthy Newbornsmentioning
confidence: 99%
“…All peripheral retinal lesions remain, therefore, unrecognized. On the other hand, various anatomical, racial, technical, and other conditions make RRT difficult for non-ophthalmologists, and false-positive screening tests are common [2]. Corneal opacity usually forms part of a complex developmental disorder of the whole anterior part of the eye (dysgenesis of the anterior segment) (Figure 1).…”
Section: New Trends In Neonatal Ophthalmic Screeningmentioning
confidence: 99%
See 1 more Smart Citation